Negative current collector and preparation method thereof, negative pole piece and lithium metal battery
By applying a mixed coating of conductive agent and boron nitride fluoride nanosheets on the negative electrode current collector of lithium metal batteries, the problems of low efficiency of lithium metal batteries and instability of the interface layer of solid electrolyte are solved, and higher energy efficiency and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411703519.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
Due to the large lattice mismatch between commercial copper current collectors and lithium metals, lithium metals, lithium dendrites have lithium sparse properties, low Coulombic efficiency, limited energy efficiency and cycle life, and the interface layer of the solid electrolyte is unstable, increasing internal resistance and accelerating performance attenuation.
A negative electrode current collector is adopted, including a current collector body and a coating on at least one side of its thickness direction. The coating consists of a conductive agent and a boron nitride fluoride nanosheet. The mass ratio of the conductive agent and boron nitride fluoride is in the range of 0.1-45:0.1-50, and the coating also includes an adhesive, and the mass ratio of the boron nitride fluoride and the adhesive is in the range of 0.1-50:1-5.
By introducing a mixed coating of boron nitride fluoride nanosheet and conductive agent, a stable solid electrolyte interface film containing LiF and Li3N is formed to improve the transmission efficiency of lithium ions, avoid the generation of lithium dendrites, and improve the first-time Coulomb efficiency and safety of the battery.
Smart Images

Figure BDA0005153962620000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a negative electrode current collector and a preparation method thereof, a negative electrode pole piece and a lithium metal battery. Background Art
[0002] As the global new energy vehicle industry enters a period of rapid development, traditional lithium-ion batteries (LIBs) can no longer meet the current market demand for high energy density and low-cost energy storage devices. Lithium metal batteries (LMBs) are batteries that use lithium metal as the negative electrode active material. Due to their extremely low electrode potential and extremely high theoretical capacity, they are considered to be one of the most promising next-generation new energy storage systems and are regarded as the ultimate choice for high-energy battery negative electrode materials.
[0003] Since there is a large lattice mismatch between the commercial copper current collector and lithium metal, it leads to serious lithium-repellent properties. In addition, during the charge and discharge process, the lithium metal negative electrode has the following disadvantages: 1. The lithium metal negative electrode is prone to the growth of lithium dendrites, which may cause internal short circuits in the battery and even cause thermal runaway and safety accidents; 2. Due to the generation of lithium dendrites and "dead lithium", the coulomb efficiency of the lithium metal negative electrode may be low, which limits the energy efficiency and cycle life of the battery; 3. The reaction between lithium metal and the electrolyte may lead to the formation of an unstable solid electrolyte interface layer (SEI layer), which will increase the internal resistance of the battery, reduce efficiency, and accelerate the battery performance degradation. Summary of the invention
[0004] One of the purposes of the present invention is to provide a negative electrode current collector and a preparation method thereof, a negative electrode plate and a lithium metal battery, so as to solve the problem of low coulombic efficiency of lithium metal batteries.
[0005] In order to achieve the above objectives, the technical solution adopted by the present invention is: a negative electrode current collector for a lithium metal battery, comprising a current collector body and a coating arranged on at least one side in the thickness direction of the current collector body, wherein the coating comprises a conductive agent and fluorinated boron nitride nanosheets.
[0006] Further, the mass ratio of the conductive agent to the fluorinated boron nitride nanosheets is (0.1-45): (0.1-50). Exemplarily, the mass ratio of the conductive agent to the fluorinated boron nitride nanosheets is 0.1:0.1, 0.1:20, 0.1:50, 1:0.1, 1:20, 1:50, 20:0.1, 15:20, 20:50, 45:0.1, 45:20, 45:50 or a range consisting of any two of them.
[0007] Furthermore, the coating further comprises an adhesive, the mass ratio of the fluorinated boron nitride to the adhesive is (0.1-50):(1-5), and the adhesive is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, polytetrafluoroethylene, and polyvinyl alcohol. Exemplarily, the mass ratio of the fluorinated boron nitride to the adhesive is 0.1:1, 0.1:2, 0.1:5, 20:1, 20:2, 20:5, 50:1, 50:2, 50:5, or a range consisting of any two of them.
[0008] Furthermore, the negative electrode current collector for a lithium metal battery includes at least one of the following technical features:
[0009] (1) The thickness of the coating is 0.5 μm-5 μm; illustratively, the thickness of the coating is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range consisting of any two thereof.
[0010] (2) The diameter of the fluorinated boron nitride nanosheets is 100-2000 nm; illustratively, the diameter of the fluorinated boron nitride nanosheets is 100 nm, 200 nm, 500 nm, 1000 nm, 1500 nm, 2000 nm or a range consisting of any two of them.
[0011] (3) The conductive agent is selected from one or more of conductive carbon black, colloidal graphite, few-layer graphene, and carbon nanotubes;
[0012] (4) The current collector body is at least one of copper foil, aluminum foil, composite copper foil, and composite aluminum foil.
[0013] Further, the conductive agent is a mixture of conductive carbon black and carbon nanotubes; the mass ratio of the conductive carbon black to the carbon nanotubes is (4-9):1; the particle size of the conductive carbon black is 10-35nm, the particle size of the carbon nanotubes is 5-100nm, and the length of the carbon nanotubes is 0.1-5μm. Exemplarily, the mass ratio of the conductive carbon black to the carbon nanotubes is 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or a range consisting of any two thereof; the particle size of the conductive carbon black is 10nm, 15nm, 20nm, 25nm, 30nm, 35nm or a range consisting of any two thereof; the particle size of the carbon nanotubes is 5nm, 10nm, 20nm, 40nm, 60nm, 80nm, 100nm or a range consisting of any two thereof; and the length of the carbon nanotubes is 0.1μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm or a range consisting of any two thereof.
[0014] A method for preparing a negative electrode current collector for a lithium metal battery comprises the following steps:
[0015] S1. preparing a dispersant solution;
[0016] S2, adding a conductive agent, boron nitride fluoride, and a binder into a dispersant solution to prepare a current collector slurry;
[0017] S3, coating the slurry on the surface of the current collector body, and baking to obtain the negative electrode current collector.
[0018] Furthermore, the method for preparing the negative electrode current collector includes at least one of the following technical features:
[0019] (1) In S1, the solid content of the dispersant solution is 0.5%-5%, and the viscosity of the dispersant solution is 3000cp-15000cp;
[0020] (2) The preparation method of the dispersant solution comprises: mixing deionized water and the dispersant and stirring, the stirring temperature is 20°C-40°C, the stirring speed is 10-50rpm, the dispersion speed is 400-1000rpm, and the stirring time is 120min-300min;
[0021] (3) In S2, the step of adding the conductive agent, fluorinated boron nitride and adhesive into the dispersant solution to prepare the current collector slurry comprises: adding the conductive agent and fluorinated boron nitride nanosheets into the dispersant solution in batches and stirring, the stirring speed is 5-50 rpm, the dispersion speed is 200-800 rpm, and the stirring time is 120 min-300 min; adding N-methylpyrrolidone into the dispersant solution during the stirring process; and after the stirring is completed, adding the adhesive into the dispersant solution and stirring to prepare the current collector slurry;
[0022] Wherein, in terms of mass percentage, the N-methylpyrrolidone accounts for 0.5%-1% of the slurry; by adding N-methylpyrrolidone NMP solvent, the solubility of the solvent in the conductive agent and the fluorinated boron nitride nanosheets is improved.
[0023] (4) In the slurry, the conductive agent: fluorinated boron nitride nanosheets: adhesive: dispersant = (0.1-45): (0.1-50): (1-5): (0.1-5);
[0024] (5) Calculated by mass percentage, the solid content of the slurry is 10%-30%, and the slurry viscosity is 1500cp-9000cp;
[0025] (6) In S3, the current collector body coated with the slurry is kept in an oven at 90° C. to 120° C. for 10 s to 120 s to obtain a negative electrode current collector;
[0026] (7) In S3, the slurry prepared in S2 is coated on the upper surface and / or lower surface of the current collector body;
[0027] (8) The current collector body is at least one of copper foil, aluminum foil, composite copper foil, and composite aluminum foil.
[0028] Furthermore, the diameter of the fluorinated boron nitride nanosheets is 100-2000 nm; and / or the conductive agent is selected from one or more of conductive carbon black, colloidal graphite, few-layer graphene, and carbon nanotubes.
[0029] A negative electrode plate for a lithium metal battery comprises the negative electrode current collector as described above, or the negative electrode current collector prepared by the preparation method as described above.
[0030] A lithium metal battery comprises the negative electrode plate as described above.
[0031] The beneficial effects of the present invention are:
[0032] 1) By introducing a mixed coating of fluorinated boron nitride (F-BN) nanosheets and a conductive agent, when the negative electrode current collector is applied to a lithium metal battery, the solid electrolyte interface film (SEI film) formed on the surface of the negative electrode after the lithium metal battery is charged and discharged contains LiF and Li3N. Li3N has a higher adsorption energy and a lower ion diffusion barrier, which is conducive to the rapid transmission of lithium ions, making Li deposit evenly, avoiding its local aggregation and evolving into dendrites, and improving the first coulombic efficiency and safety of the battery.
[0033] 2) The contact angle of F-BN was measured to be 3.9°, which gives it a high surface interfacial energy, which is conducive to the formation of a stable SEI film and promotes rapid ion transport, further reducing Li deposition.
[0034] 3) Both F-BN and LiF have high interfacial stability of electron tunneling barrier. The ionic conductivity of F-BN is 1.4×10 -3 S cm -1 , the ion transfer number is as high as 0.73. High ionic conductivity and ion transfer number can accelerate Li + The transmission in the negative electrode sheet is conducive to uniform and dense lithium deposition and prevents the formation of lithium dendrites. The low electronic conductivity of F-BN can also prevent electrons from tunneling through the SEI film, prevent the decomposition of the SEI film and the parasitic reaction between the SEI film and other substances in the negative electrode, and improve the stability of the solid electrolyte interface film (SEI film), thereby improving the first coulombic efficiency of the battery. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0036] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0037] An embodiment of the present invention provides a negative electrode current collector, which specifically includes the following preparation steps:
[0038] S1. preparing a dispersant solution;
[0039] The solid content of the dispersant solution is 0.5%-5%, and the viscosity of the dispersant solution is 3000cp-15000cp.
[0040] The preparation method of the dispersant solution comprises: adding deionized water and dispersant and stirring, wherein the mass ratio of the dispersant to deionized water is 0.5%-5%:99.5%-95%. Deionized water and dispersant are added in 2-3 times, stirring is performed while adding, the stirring temperature is controlled at 20°C-40°C, the stirring speed is 10-50rpm, the dispersing speed is 400-1000rpm, and the stirring time is 120min-300min. Then vacuuming and stirring slowly, testing the viscosity and solid content of the dispersant solution, the solid content of the dispersant solution is 0.5%-5%, and the viscosity of the dispersant solution is 3000cp-15000cp.
[0041] In some embodiments, the dispersant is selected from one or more of carboxymethyl cellulose (CMC), hydrogenated nitrile rubber (HNBR), and polyacrylate (PAA).
[0042] S2, adding a conductive agent, boron nitride fluoride, and a binder into a dispersant solution to prepare a current collector slurry;
[0043] The step of adding the conductive agent, the fluorinated boron nitride and the adhesive into the dispersant solution to prepare the current collector slurry comprises: adding the conductive agent and the fluorinated boron nitride nanosheets into the dispersant solution in batches and stirring, the stirring speed is 5-50 rpm, the dispersion speed is 200-800 rpm, and the stirring time is 120 min-300 min; adding N-methylpyrrolidone into the dispersant solution during the stirring process; and adding the adhesive into the dispersant solution after the stirring is completed, stirring, to prepare the current collector slurry;
[0044] In some embodiments, the fluorinated boron nitride nanosheets have a diameter of 100-2000 nm.
[0045] In some embodiments, the conductive agent is selected from one or more of conductive carbon black, colloidal graphite, few-layer graphene, and carbon nanotubes.
[0046] In some embodiments, the conductive agent is a mixture of conductive carbon black and carbon nanotubes, the conductive carbon black particle size is 10-35 nm, the carbon nanotube particle size is 5-100 nm, and the carbon nanotube length is 0.1-5 μm.
[0047] In some embodiments, the mass ratio of the conductive carbon black to the carbon nanotubes is 8:2 to 9:1.
[0048] In some embodiments, the adhesive is selected from one or more of polyvinylidene fluoride PVDF, styrene butadiene rubber SBR, LA132 water-based adhesive, LA133 water-based adhesive, polytetrafluoroethylene PTFE, and polyvinyl alcohol PVA.
[0049] In some embodiments, the solid content of the prepared slurry is 10%-30% by mass, and the slurry viscosity is 1500cp-9000cp.
[0050] In some embodiments, in the slurry, by weight, conductive agent: fluorinated boron nitride nanosheets: binder: dispersant = (0.1-45): (0.1-50): (1-5): (0.1-5);
[0051] In some embodiments, the N-methylpyrrolidone accounts for 0.5%-1% of the slurry by mass.
[0052] S3, coating the slurry on the surface of the current collector body, and baking to obtain the negative electrode current collector.
[0053] The slurry prepared in S2 is coated on the upper and lower surfaces of the current collector body, and the current collector body coated with the slurry is kept in an oven at 90° C.-120° C. for 10s-120s to obtain a negative electrode current collector with a coating thickness of 0.5 μm-5 μm.
[0054] The current collector body is at least one of copper foil, aluminum foil, composite copper foil and composite aluminum foil. Both the composite aluminum foil and the composite copper foil have a three-layer structure, including a first conductive layer, a second polymer insulating layer and a third conductive layer. The polymer layer material of the second layer is selected from any one of PET, PP and PI. The conductive layer material of the composite aluminum foil is aluminum, and the conductive layer material of the composite copper foil is copper.
[0055] The present embodiment also provides a negative electrode plate of a lithium metal battery, the negative electrode plate includes a negative electrode collector and a negative electrode active layer arranged on the negative electrode collector, the negative electrode collector is a collector coated with a fluorinated boron nitride coating according to the present invention, the material of the negative electrode active layer is lithium metal, and the thickness of the lithium metal is 30μm-500μm.
[0056] This embodiment also provides a lithium metal battery, including a positive electrode sheet, the negative electrode sheet described in the above embodiment, and a solid electrolyte disposed between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on the positive electrode current collector, the positive electrode current collector is made of aluminum foil, and the positive electrode active layer is made of lithium iron phosphate. The material of the solid electrolyte is lithium oxide garnet.
[0057] Example
[0058] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0059] Example 1
[0060] A method for preparing a negative electrode current collector comprises the following steps:
[0061] S1. preparing a dispersant solution;
[0062] The dispersant is carboxymethyl cellulose CMC. By weight, the dispersant solution includes 2 parts of CMC and 73 parts of deionized water. Deionized water and dispersant are added in 3 times, stirring speed is 30rpm, dispersing speed is 1000rpm, and time is 4h. The tank temperature is controlled at 30℃, and then vacuumed and stirred slowly, with a vacuum degree of -75kpa to -95kpa. The viscosity and solid content of the dispersant solution are tested. The solid content of the dispersant is 2.8% and the viscosity is 10000cp.
[0063] S2, adding a conductive agent, boron nitride fluoride, and a binder into a dispersant solution to prepare a current collector slurry;
[0064] Specifically, by weight, 20 parts of conductive agent and 1 part of fluorinated boron nitride (F-BN) nanosheets were added to the carboxymethyl cellulose CMC glue, mixed and stirred at a stirring speed of 20 rpm, a dispersion speed of 600 rpm, stirred for 2 hours, and a tank temperature of 30° C. During the stirring process, 1 part of N-methylpyrrolidone NMP solvent was added.
[0065] Add 3 parts of adhesive styrene-butadiene rubber SBR, stir at 15 rpm, disperse at 500 rpm, tank temperature at 30°C, stir for 30 minutes to prepare a slurry for the current collector; test the viscosity and solid content of the slurry, the solid content is 26%, and the viscosity is 8000 cp.
[0066] The conductive agent material is composed of conductive carbon black SP and carbon nanotubes CNT in a mass ratio of 8:2, the SP particle size is 10-35nm, the CNT particle size is 5-100nm, and the length is 0.1-5μm.
[0067] S3, coating the slurry on the surface of the current collector body, and baking to obtain the negative electrode current collector.
[0068] The slurry prepared in S2 was coated on the surface of traditional pure copper foil and composite copper foil respectively, and kept in a hot air oven at 100°C for 160S, finally obtaining a negative electrode current collector with a coating layer thickness of 1 μm.
[0069] Example 2
[0070] The preparation methods of Example 2 and Example 1 are basically the same, the main difference being that the number of added fluorinated boron nitride (F-BN) nanosheets is 2 parts and the number of added deionized water is 72 parts.
[0071] Example 3
[0072] The preparation methods of Example 3 and Example 2 are basically the same, the main difference being that the added conductive agent material consists of conductive carbon black SP and carbon nanotubes CNT in a mass ratio of 9:1.
[0073] Example 4
[0074] The preparation methods of Example 4 and Example 1 are basically the same, the main difference being that the added conductive agent material consists of conductive carbon black SP and carbon nanotubes CNT in a mass ratio of 9:1.
[0075] Example 5
[0076] The preparation methods of Example 5 and Example 1 are basically the same, the main differences being that the amount of the conductive agent added is 20.5 parts, and the amount of the fluorinated boron nitride (F-BN) nanosheets added is 0.5 parts.
[0077] Example 6
[0078] The preparation methods of Example 6 and Example 1 are basically the same, the main differences being that the amount of the conductive agent added is 19.5%, the amount of the fluorinated boron nitride (F-BN) nanosheets added is 2.5%, and the amount of deionized water is 72 parts.
[0079] Example 7
[0080] The preparation methods of Example 7 and Example 5 are basically the same, the main difference being that the added conductive agent material consists of conductive carbon black SP and carbon nanotubes CNT in a mass ratio of 9:1.
[0081] Example 8
[0082] The preparation methods of Example 8 and Example 6 are basically the same, the main difference being that the added conductive agent material consists of conductive carbon black SP and carbon nanotubes CNT in a mass ratio of 9:1.
[0083] Comparative Example 1
[0084] The negative electrode current collector is a conventional pure copper foil without slurry coating.
[0085] Comparative Example 2
[0086] The negative electrode current collector is a composite copper foil current collector without slurry coating.
[0087] Experimental Example 1
[0088] Lithium metal solid-state batteries were prepared using the negative electrode current collectors in Examples 1-8 and the negative electrode current collectors in Comparative Examples 1-2, and the batteries were subjected to performance tests. The performance test results are shown in Table 1.
[0089] Among them, the lithium metal solid-state battery includes a positive electrode plate, a negative electrode plate, and a solid electrolyte arranged between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode collector and a positive electrode active layer arranged on the positive electrode collector, the material of the positive electrode collector is aluminum foil, and the material of the positive electrode active layer is lithium iron phosphate. The material of the solid electrolyte is lithium oxide garnet. The negative electrode plate includes a negative electrode collector and a negative electrode active layer arranged on the negative electrode collector, the negative electrode collector is a current collector coated with a fluorinated boron nitride coating according to the present invention, and the material of the negative electrode active layer is lithium metal.
[0090] The test method for the first coulombic efficiency is as follows: (1) Charging: Connect the test sample to a constant current source and charge at a charging rate of 1C. After constant current charging to the cut-off voltage, switch to constant voltage charging, and directly reduce the charging current to 0.05C. Record the voltage, current and time of the sample during the entire charging process; (2) Standing: After charging, let the battery stand for 30 minutes; (3) Discharging: Connect the fully charged test sample to a load and discharge at a discharge rate of 1C until the set cut-off voltage is reached. Record the voltage, current and time of the sample during the entire discharge process; (4) Calculate the charging capacity and the discharging capacity; (5) Calculate the first coulombic efficiency, where the first coulombic efficiency = (discharge capacity / charge capacity) × 100%.
[0091] The DCR test method at 50% SOC is as follows: (1) Charge the battery to 50% SOC using a constant current charging method. During this process, the battery voltage and current need to be monitored to ensure that 50% SOC is accurately reached; (2) Let the battery rest for 30 minutes; (4) After the rest period, record the battery's open circuit voltage V0; (5) Discharge the battery for a short time at a current rate of 1C for 10 seconds. During the discharge process, record the battery voltage change. (6) At the end of the discharge, record the battery voltage V1; (7) Use the following formula to calculate the DC internal resistance (DCR): DCR = |V0-V1| / I, where V0 is the open circuit voltage before discharge, V1 is the voltage at the end of discharge, and I is the discharge current.
[0092] The test method for the discharge capacity retention rate is as follows: (1) subject the battery to three standard charge and discharge cycles to stabilize the battery performance and determine the initial capacity C1; (2) after fully charging the battery, store it at room temperature for 28 days; (3) after the storage period, discharge it at the standard discharge rate and record the discharge capacity (C2); (4) calculate the discharge capacity retention rate using the following formula: Capacity retention rate = (C2 / C1) × 100%.
[0093] The test method for the 1C cycle number is as follows: (1) Use a constant current and constant voltage charging device to charge the battery at a current of 1C. When the battery terminal voltage reaches 4.2V, change to constant voltage charging until the charging current is reduced to 0.05C or lower; (2) After charging, let the battery stand for 0.5 to 1 hour; (3) Use a discharge test device to discharge at a current of 1C to a termination voltage of 2.75V; after discharge, let it stand for another 0.5 to 1 hour; (4) Cycle test: Repeat the above charge and discharge steps until the battery discharge time is less than 36 minutes twice, and record the number of cycles at this time.
[0094] Table 1: Comparison of lithium battery initial efficiency, DCR, discharge capacity retention rate and ultimate charging capacity
[0095]
[0096] The performance of lithium metal solid-state batteries prepared using the current collectors in Examples 1-8 and the current collectors in Comparative Examples 1-2 was tested. The test results showed that the battery prepared using the current collector prepared in Example 1 had better effects, better charge-discharge and cycle performance, and the first efficiency could reach 94.2%, the DCR at 50% SOC was 10mΩ, and the cycle life under 1C charge-discharge conditions could reach more than 400 times. Compared with Example 1, in Examples 2-8, although the first efficiency and discharge capacity retention rate decreased, the first efficiency could still be maintained at about 90%, and the discharge capacity retention rate was greater than 90%.
[0097] From the data of Comparative Examples 1 and 2, it can be seen that the current collector currently used as a lithium metal negative electrode material has a cycle life of less than 100 times, the first efficiency is less than 80%, and the discharge capacity retention rate is just over 80%, which are all less than the first efficiency and discharge capacity retention rate of the battery prepared by the current collector. By coating the slurry on the surface of the traditional pure copper foil and composite copper foil in Comparative Examples 1 and 2 and preparing the current collector, the first coulomb efficiency, discharge capacity retention rate and cycle performance of the battery are improved. Therefore, the current collector for solid-state batteries provided by the present invention and its preparation method are conducive to improving the first coulomb efficiency and cycle performance of the battery, and the cycle life is more than 200 times under 1C conditions.
[0098] The capacity retention rate and cycle life of the composite copper foil lithium metal negative electrode solid-state battery prepared using the current collector are higher than those of the traditional pure copper foil. The reasons are: during the charging and discharging process of the lithium metal solid-state battery, the volume of the negative electrode plate changes, and the addition of boron nitride fluoride enhances the lithium ion transmission efficiency and increases the volume change of the negative electrode plate; the elastic modulus of the composite copper foil is significantly lower than that of the traditional pure copper foil, and the plastic deformation of the composite current collector effectively weakens its constraint on the active layer, which makes the stress in the composite current collector and the active layer significantly relieved during the volume change of the negative electrode plate during the charging and discharging of the lithium metal solid-state battery, avoiding the occurrence of high stress at the interface of the active layer, improving the mechanical reliability of the plate during the charging process, and avoiding the cracking and failure of the negative electrode plate due to stress concentration, thereby extending the cycle life of the battery; at the same time, the relaxation effect of the plastic deformation of the composite current collector also promotes the diffusion of lithium in the active layer, which allows more lithium to enter the active material and improves the discharge capacity retention rate.
[0099] Therefore, the present invention introduces a mixed coating of fluorinated boron nitride (F-BN) nanosheets and a conductive agent. When the negative electrode current collector is applied to a lithium metal battery, the solid electrolyte interface film (SEI film) formed on the surface of the negative electrode after the lithium metal battery is charged and discharged contains LiF and Li3N. Li3N has a high adsorption energy and a low ion diffusion barrier, which is conducive to the rapid transmission of lithium ions, making Li deposit uniformly, avoiding its local aggregation and evolution into dendrites, and improving the first coulomb efficiency and safety of the battery. The contact angle of F-BN was measured to be 3.9°. This high surface interface energy is conducive to the formation of a stable SEI film and promotes rapid ion transmission, further reducing Li deposition. Both the F-BN substrate and LiF have interface stability with high electron tunneling barriers. The ionic conductivity of F-BN is 1.4×10 -3 S cm -1 , the ion transfer number is as high as 0.73. High ionic conductivity and ion transfer number can accelerate Li + The transmission in the negative electrode sheet is conducive to uniform and dense lithium deposition and prevents the formation of lithium dendrites. The low electronic conductivity of F-BN can also prevent electrons from tunneling through the SEI film, preventing the decomposition of the SEI film and the polymerization reaction of the SEI film with other substances in the negative electrode, thereby improving the first coulombic efficiency of the battery.
[0100] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode current collector for a lithium metal battery, characterized in that: The invention comprises a current collector body and a coating arranged on at least one side of the current collector body in a thickness direction, wherein the coating comprises a conductive agent and fluorinated boron nitride nanosheets.
2. The negative electrode current collector for a lithium metal battery according to claim 1, characterized in that: The mass ratio of the conductive agent to the fluorinated boron nitride nanosheets is (0.1-45): (0.1-50).
3. The negative electrode current collector for a lithium metal battery according to claim 1, characterized in that: The coating also includes an adhesive, the mass ratio of the fluorinated boron nitride to the adhesive is (0.1-50): (1-5), and the adhesive is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, polytetrafluoroethylene, and polyvinyl alcohol.
4. The negative electrode current collector for a lithium metal battery according to any one of claims 1 to 3, characterized in that: Include at least one of the following technical features: (1) The thickness of the coating is 0.5 μm-5 μm; (2) The diameter of the fluorinated boron nitride nanosheets is 100-2000 nm; (3) The conductive agent is selected from one or more of conductive carbon black, colloidal graphite, few-layer graphene, and carbon nanotubes; (4) The current collector body is at least one of copper foil, aluminum foil, composite copper foil, and composite aluminum foil.
5. The negative electrode current collector for a lithium metal battery according to claim 4, characterized in that: The conductive agent is a mixture of conductive carbon black and carbon nanotubes; the mass ratio of the conductive carbon black to the carbon nanotubes is (4-9):1; the particle size of the conductive carbon black is 10-35nm, the particle size of the carbon nanotubes is 5-100nm, and the length of the carbon nanotubes is 0.1-5μm.
6. A method for preparing a negative electrode current collector for a lithium metal battery, characterized in that: The steps include: S1. preparing a dispersant solution; S2, adding a conductive agent, boron nitride fluoride, and a binder into a dispersant solution to prepare a current collector slurry; S3, coating the slurry on the surface of the current collector body, and baking to obtain the negative electrode current collector.
7. The method for preparing a negative electrode current collector according to claim 6, characterized in that: Include at least one of the following technical features: (1) In S1, the solid content of the dispersant solution is 0.5%-5%, and the viscosity of the dispersant solution is 3000cp-15000cp; (2) The preparation method of the dispersant solution comprises: mixing deionized water and the dispersant and stirring, the stirring temperature is 20°C-40°C, the stirring speed is 10-50rpm, the dispersion speed is 400-1000rpm, and the stirring time is 120min-300min; (3) In S2, the step of adding the conductive agent, fluorinated boron nitride and adhesive into the dispersant solution to prepare the current collector slurry comprises: adding the conductive agent and fluorinated boron nitride nanosheets into the dispersant solution in batches and stirring, the stirring speed is 5-50 rpm, the dispersion speed is 200-800 rpm, and the stirring time is 120 min-300 min; adding N-methylpyrrolidone into the dispersant solution during the stirring process; and after the stirring is completed, adding the adhesive into the dispersant solution and stirring to prepare the current collector slurry; Wherein, according to mass percentage, the N-methylpyrrolidone accounts for 0.5%-1% of the slurry; (4) In the slurry, according to the mass ratio, the conductive agent: the fluorinated boron nitride nanosheets: the adhesive: the dispersant = (0.1-45): (0.1-50): (1-5): (0.1-5); (5) Calculated by mass percentage, the solid content of the slurry is 10%-30%, and the slurry viscosity is 1500cp-9000cp; (6) In S3, the current collector body coated with the slurry is kept in an oven at 90° C. to 120° C. for 10 s to 120 s to obtain a negative electrode current collector; (7) In S3, the slurry prepared in S2 is coated on the upper surface and / or lower surface of the current collector body; (8) The current collector body is at least one of copper foil, aluminum foil, composite copper foil, and composite aluminum foil.
8. The method for preparing a negative electrode current collector according to claim 7, characterized in that: The diameter of the fluorinated boron nitride nanosheets is 100-2000nm; and / or the conductive agent is selected from one or more of conductive carbon black, colloidal graphite, few-layer graphene, and carbon nanotubes.
9. A negative electrode sheet for a lithium metal battery, comprising the negative electrode current collector according to any one of claims 1 to 5, or the negative electrode current collector prepared by the preparation method according to any one of claims 6 to 8.
10. A lithium metal battery comprising the negative electrode sheet according to claim 9.